IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL DI KANTOR CAMAT TELEN KABUPATEN KUTAI TIMUR - Andi Sulviana Sultan (Jurnal Paradigma (JP), 2018)
The purpose of this study is to describe and analyze the implementation of government regulation No. 53  2010 about the Discipline of government civil servants. The Source of data is taken from the informants and the key informant and supported by the primary and secondary data. Meanwhile, the key informant is the head of subdistrict Telen East Kutai Regency. The Analysis of the data used is interactive model. The result of the research shows that the Discipline of government civil servants in the subdistrict office Telen East Kutai Regency regulated based on government regulation No. 53  2010 is implemented less effectively.